Delineating nonmelanoma skin cancer margins using terahertz and optical imaging - Anna N. Yaroslavsky; Cecil Joseph; Rakesh Patel; Alona Muzikansky; Victor A. Neel; Robert H. Giles (Journal of Biomedical Photonics & Engineering, 2017)
We evaluated terahertz reflectance imaging and a combination of terahertz and optical techniques for delineating nonmelanoma skin cancers. After imaging, each terahertz pixel of each specimen was classified as cancerous or normal using a previously determined threshold. Subsequently, cancerous terahertz pixels were re-evaluated with polarization-sensitive optical technique. This additional information enabled us to re-classify each cancerous terahertz pixel using morphological appearance of the structures in the optical images. If the structures in the terahertz pixel appeared normal, the pixel was considered normal. The generalized linear mixture model was implemented to determine the sensitivity and specificity of each method. The model tested the probability of each terahertz pixel being diagnosed as a match with histology. For terahertz imaging alone, the sensitivity and specificity were 82% and 94%, respectively. For multimodal imaging, the sensitivity and specificity increased to 96 % and 99%, respectively. Multimodal terahertz-optical imaging has potential for the intraoperative assessment of tumor margins.